Mandatory CSR reporting and disability employment. Evidence from India - Kofi Mintah Oware (Cogent Business & Management, 2023)
The purpose of the study is to examine whether mandatory CSR reporting affects the disability employment of listed firms and whether a family(non) management firm's perspective matter in the Indian context. From 2009 to 2020, the data set includes 80 firms with 960 firm-year observations, including 783 firm-year observations for family-managed firms and 177 firm-year observations for non-family-managed firms on the Indian stock exchange. Panel regression with random effect assumptions and probit regression are the research models for examining the study. The first findings show that mandatory CSR reporting increases the disability employment of listed firms in India. The second findings show that mandatory CSR reporting has a positive and statistically significant association with disability employment of family firms in India. Similarly, the third findings show that mandatory CSR reporting has a positive and statistically significant association with disability employment of non-family firms in India. However, the magnitude effect expressed in the beta coefficient is higher in non-family firms than in family firms. Our findings are unaffected by firm-level characteristics. Our research adds to the discussion of factors that influence disability employment by providing fresh information on required CSR reporting, which has been investigated in prior studies.
Keywords: 650; Disability employment; family(non) management; India; Mandatory CSR reporting